2022
DOI: 10.1021/acs.analchem.2c03217
|View full text |Cite
|
Sign up to set email alerts
|

Robust DNA Cross-Linked Polymeric Lighting-Up Nanogel Facilitates Sensitive Live Cell MicroRNA Imaging

Abstract: Accurate and specific imaging of low-abundance intracellular microRNAs (miRNAs) is crucial for monitoring cellular processes and disease diagnosis. Despite the fact that nucleic acid amplification technologies have shown great advantages for the detection of trace targets, their live cell imaging applications remain a major challenge because of the insufficient stability and slow reaction kinetics of the probes in cellular delivery and imaging. Herein, we demonstrate the synthesis of DNA-cross-linked polymeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…11,12 Accurate imaging of intracellular diseases-related miRNAs is of great value for early diagnosis, sensitive monitoring, timely treatment and effective prognosis of diseases. 13 Nevertheless, owing to the small size and low expression level of miRNAs and the complex cytoplasmic environment, achieving accurate imaging of miRNA in living cells remains a huge challenge. 14−16 Although fluorescence in situ hybridization (FISH) is a commonly used method to visualize specific DNA or RNA molecules in a cell or tissue, it is not suitable for low-expressed miRNA due to the insufficient sensitivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11,12 Accurate imaging of intracellular diseases-related miRNAs is of great value for early diagnosis, sensitive monitoring, timely treatment and effective prognosis of diseases. 13 Nevertheless, owing to the small size and low expression level of miRNAs and the complex cytoplasmic environment, achieving accurate imaging of miRNA in living cells remains a huge challenge. 14−16 Although fluorescence in situ hybridization (FISH) is a commonly used method to visualize specific DNA or RNA molecules in a cell or tissue, it is not suitable for low-expressed miRNA due to the insufficient sensitivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…30 The DNA triggers can initiate the HCR to generate highly elongated dsDNA polymers, thereby achieving signal amplification for detecting target molecules. 31 A number of studies have reported the integration of the HCR with aptamer sensors, and their detection sensitivities are greatly increased, due to the benefits of the HCR. [32][33][34] As a representative technique for nucleic acid amplification without the need for enzymes, the HCR has the ability to both enrich signal probes through nucleic acid extension and utilize RCA products to further amplify the signal.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous report, DNA incorporated in a nanoscale network may improve the collision efficiency and enhance the signal response of DNA. 30,31 Therefore, the UCPD microgels with enhanced activities than DNA decorated rigid nanoparticles may show great potential as functional DNA carriers.…”
mentioning
confidence: 99%